Integration of romani people, as the most important internal political problems of Hungary - István Süli-Zakar; Ágnes Pálóczi; Tibor Kóti (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The intense population growth of romani people as a result of which every tenth Hungarian citizen will be romani within a few years. However, in contrast of the aging Hungarian society romani population represents a youthful group which unambiguously seems more-and-more significant both in political and human resource aspects. It is generally known that a considerable proportion of Romani people inHungarylive on welfare grants. This, besides that the social and economic integration of romani people, the so-called “romani issue” became a hot political issue, also means a serious burden on the society. This is due to the differences in values, their problems in erudition and mode of life, the bias of the majority of citizens against romani people which can be eliminated or at least reduced by accelerating integration processes. The authors believe that the socio-geographical studies of Romani people, besides the remarkable sociological and romological achievements so far, can give an efficient tool for identifying and solving the problems.